2020
DOI: 10.3390/toxins12040258
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Target Fishing Approach to Identify Novel Ochratoxin A Hydrolyzing Enzyme

Abstract: Ochratoxin A (OTA), a mycotoxin that is of utmost concern in food and feed safety, is produced by fungal species that mainly belong to the Aspergillus and Penicillium genera. The development of mitigation strategies to reduce OTA content along the supply chains is key to ensuring safer production of food and feed. Enzyme-based strategies are among the most promising methods due to their specificity, efficacy, and multi-situ applicability. In particular, some enzymes are already known for hydrolyzing OTA into o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Drying was conducted at 55 • C for 24 h [54]. Subsequently, the filter paper and mycelium were removed and then weighed to achieve the total weight m 2 of the mycelium and filter paper [55]. The mycelial dry weight m 3 was calculated as (3):…”
Section: Effect Of Stress On the Surface Structure And Growth Of The Myceliummentioning
confidence: 99%
“…Drying was conducted at 55 • C for 24 h [54]. Subsequently, the filter paper and mycelium were removed and then weighed to achieve the total weight m 2 of the mycelium and filter paper [55]. The mycelial dry weight m 3 was calculated as (3):…”
Section: Effect Of Stress On the Surface Structure And Growth Of The Myceliummentioning
confidence: 99%
“…OTalpha is described as the main metabolite resulting from detoxification, and it has been shown to be mostly produced by gut microbiota. However, non-microbial carboxypeptidases have also been described to hydrolyse OTA to OTalpha, including the bovine carboxypeptidase A and the porcine ortholog carboxypeptidase B [ 15 , 19 , 20 ]. Hydroxylation on the isocoumarin portion of OTA leading to 4-(R/S)-hydroxy-OTA -and 10-OH-OTA has been described from in vitro and in vivo studies as a minor metabolic route, and CYP2D6 together with CYP2B6 have been shown to be involved in the formation of these hydroxy metabolites [ 15 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ingested OTA can easily be absorbed and further distributed to different organs. Nevertheless, natural detoxification into less-/nontoxic metabolites, such as ochratoxin alpha (OTα) and phenylalanine, is possible by enzymes and microbes in the gut [ 17 , 18 , 19 ]. The concentration of OTA metabolites in biological samples is dependent on the OTA dose and exposure time, and generally lower compared to measured OTA concentrations in feed.…”
Section: Introductionmentioning
confidence: 99%